Effect of compound dimple on tribological performances of journal bearing. (November 2015) - Meng, F.M.; Zhang, L.; Liu, Y.; Li, T.T.
Abstract: The effect of the compound dimple on the tribological performances of a journal bearing is studied. In doing so, the tribological performances for the bearing with the compound dimple and simple dimple are studied using a fluid structure interaction (FSI) method and compared further. Numerical results show that the compound dimple can supply the larger load-carrying capacity and lower friction coefficient due to its twice hydrodynamic action in comparison with the simple dimple. Moreover, the above improvement depends on the geometry sizes of the compound dimple, the dimple interval, and working parameters of the bearing. Highlights: ● We propose a compound dimple concept to reduce friction. ● The compound dimple is preferable to the simple dimple. ● The compound dimple will yield twice the hydrodynamic action.